Oropharyngeal dysphagia in extrapyramidal syndrome - ferdinand simanjuntak; Rery Budiarti; Muyassaroh - (Oto Rhino Laryngologica Indonesiana, 2021)
Background: Dysphagia could be caused by mechanical or motoric problems. Dysphagia is associated with neurological disorders in extrapyramidal syndrome (EPS), including tardive dyskinesia caused by long-term chronic use of antipsychotic drugs. Dysphagia in EPS about 9.4% occurs in young adults. Dysphagia in EPS could be a single symptom or as an concomitant symptom. Purpose: To discuss a case of oropharyngeal dysphagia in EPS due to the effects of antipsychotic drugs on a patient who was treated under multidisciplinary management. Case report: A 32-year-old male patient came to Emergency Unit of Dr.Kariadi Hospital with chief complaint of a sudden onset of difficulty in swallowing liquid and solid food. He had a history of longterm use of Chlorpromazine. The diagnosis of oropharyngeal dysphagia was established with Fiberoptic Endoscopic Evaluation of Swallowing (FEES). Clinical question: What is the proper management for dysphagia in EPS? Method: Literature search through database Pubmed and Google Scholar found 88 journals. Results: There were 4 journals relevant with the case. Those journals reviewed the diagnosis and disclosed the management of EPS with dysphagia was discontinuation of the analogous antipsychotic drugs and swallowing practice physiotherapy. Conclusion: Dysphagia in this case was an EPS due to chlorpromazine use, and made a good respond after drug replacement.ABSTRAK Latar belakang: Disfagia dapat disebabkan oleh gangguan mekanik maupun motorik. Disfagia dapat berhubungan dengan kelainan neurologis pada sindrom ekstrapiramidal (SEP), antara lain tardive diskinesia yang disebabkan pemakaian obat antipsikotik jangka panjang. Disfagia pada SEP sekitar 9,4 % terjadi pada usia dewasa muda. Disfagia pada SEP dapat merupakan gejala tunggal atau sebagai gejala penyerta. Tujuan: Membahas kasus disfagia orofaringeal pada SEP akibat efek obat antipsikotik pada pasien yang diterapi secara multidisipliner. Laporan kasus: Seorang laki-laki usia 32 tahun datang ke IGD RSUP Dr. Kariadi dengan keluhan utama mendadak tidak dapat menelan sama sekali, baik cairan maupun makanan padat. Didapatkan tanda gejala SEP dengan riwayat pemakaian chlorpromazine jangka panjang. Diagnosis disfagia orofaringeal ditegakkan dengan pemeriksaan Fiberoptic Endoscopic Evaluation of Swallowing (FEES). Pertanyaan klinis: Bagaimana penatalaksanaan yang tepat untuk kasus disfagia pada sindrom ekstrapiramidal? Metode: Penelusuran kepustakaan melalui database Pubmed dan Google Scholar diperoleh 88 jurnal. Hasil: Didapatkan 4 jurnal yang relevan dengan kasus. Empat jurnal tersebut menyatakan tatalaksana disfagia dengan SEP ialah dilakukan penghentian obat antipsikotik tipikal dan latihan menelan. Kesimpulan: Disfagia pada SEP akibat penggunaan chorpromazine memberikan respon baik setelah dilakukan penggantian obat.Kata kunci: disfagia orofaringeal, sindrome ekstrapiramidal, chlorpromazine